2007
DOI: 10.1111/j.1742-7843.2007.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Atropine Therapy Strategies on Fenthion‐Induced Organ Dysfunction in Rats

Abstract: Abstract:We studied the influence of dose and timing of atropine therapy on fenthion-induced organ dysfunction. Thirtysix rats were randomized into six groups. All rats in the five groups except the control group were intoxicated with fenthion. The high-dose atropine group received 2 mg/kg of atropine, whereas the low-dose group received 100 µ g/kg of atropine every hour for 24 hr. One group received 2 mg/kg of atropine in the first 4 hr of intoxication while the other group received 2 mg/kg of atropine in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…If lung changes were due to aspiration, lung changes would be seen only in rabbits that aspirated fenthion and the lung changes seen in group 2 wouldn't be uniform among rabbits. In addition, studies have shown that subcutaneous administration of fenthion causes lung injury (19,32). For these reasons, we believe that the changes were due to systemic absorption of fenthion.…”
Section: Discussionmentioning
confidence: 96%
“…If lung changes were due to aspiration, lung changes would be seen only in rabbits that aspirated fenthion and the lung changes seen in group 2 wouldn't be uniform among rabbits. In addition, studies have shown that subcutaneous administration of fenthion causes lung injury (19,32). For these reasons, we believe that the changes were due to systemic absorption of fenthion.…”
Section: Discussionmentioning
confidence: 96%